In silico estrogen-like activity and in vivo osteoclastogenesis inhibitory effect of Cicer arietinum extract - Sayed, Amany A.; Elfiky, Abdo A. (Cellular and Molecular Biology, 2018)
Postmenopausal osteoporosis is a common disorder accompanied with estrogen deficiency in women. Plants containing phytoestrogens and amino acids have been used in the osteoporosis treatment. The present study aims to evaluate the estrogen-like activity of the Cicer arietinum extract (CAE) and its ability to inhibit osteoclastogenesis process. These achieved by investigating the binding of its active phytoestrogens (genistein, daidzein, formononetin and biochanin A) to the estrogen receptors (ER) Î± and Î² of rats and human in silico. In addition, in vivo study on ovariectomized (OVX) rats is performed. For in vivo study, twenty four rats were divided into four groups (n= 6). Group I is the sham control rats which administered distilled water. Groups II, III, and IV are OVX groups which administered distilled water, CAE (500 mg/kg), and alendronate; respectively. The docking study revealed that the phytoestrogens docked into the protein active site with binding energies comparable with that of estrogens (estriol and Î²-estradiol) which means the similarity between the estrogenic contents of CAE and the ensogenous ones. Additionally, in vivo study revealed that CAE reverse TRAP5b and RANKL levels that drastically increased in the untreated OVX group. But, it trigger upregulation of OPG, enhance the OPG/RANKL ratio and modulate the bone and uterus alterations of OVX group. Phytoestrogens and the bone-protective amino acids contents of CAE could be responsible for their estrogen-like effect and antiosteoporotic activity. These results concluded that CAE is an attractive candidate for developing a potential therapeutic cheap agent used as an alternative to the synthetic estrogen replacement therapy. Further, in vivo validation is required for its clinical application.